Measuring innovation performance of developing regions: learning and catch-up in provinces of Iran - Ghazinoory, Sepehr; Riahi, Parisa; Azar, Adel; Miremadi, Tahereh (Technological and Economic Development of Economy, 2014)
Common innovation performance measures, which are based on research and development activities, are not relevant to dominant innovation behaviour of developing countries. The main functions of the innovation system of developing countries are capture, imitation, learning by doing and diffusion of knowledge, to reduce technology gaps with technology frontiers. Hence, the purpose of measuring innovation performance in a developing geographical area should be the evaluation on its success in technological learning and catching-up. Using the learning and technology gap concepts, in this paper we develop a novel model of measuring innovation performance of developing countries/regions, based on common regional statistics. In the virtual absence of mandatory firm level surveys, this model can provide a useful method to compare the innovation behaviour of regions for policymaker. Running the model with the data from the Iranian provinces, the paper concludes each province has its own specific innovation behaviour stemming from different historical development paths and geographical characteristics.